Analgesik dan Anti-Inflamasi pada Cedera Sprain Pergelangan Kaki: Evidence Based Case Report - Chikih Chikih; Nani Cahyani Sudarsono (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Introduction: Ankle sprain injury is an injury that often occurs in sports activities with an incidence up to 40%. The main management is by doing conservative management in the form of RICE and strengthening exercises. However, over time, many doctors and athletes use analgesics and anti-inflammatory drugs to treat the perception of pain and swelling. This article aims to find the latest evidence-based medicine on the use of analgesics and anti-inflammatory drugs relevant to ankle sprain injuries. Methods: The study was conducted by Evidence Base Medicine approach. Literature search from two digital databases; PubMed and Cochrane and selection based on Prism Flow Charts with inclusion and exclusion criteria. No statistical analysis was performed in this study. Results: The investigation was obtained six studies, consisting of 5 systematic review studies discussing the use of NSAIDs, Opioids, Acetaminophen and Cox-inhibitors in ankle sprain injury patients. The use of NSAIDs was less edible than the use of placebo and there was no significant difference between the use of NSAIDs and other analgesics. Topical use has a perceived better effectiveness than oral NSAID use. Conclusion: The use of analgesics in case of ankle sprain injury still needs further research; the main consideration is based on the patient’s pain perception. Conservative therapy remains the mainstay.